2019
DOI: 10.1149/2.0151916jes
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of High Performance and Ultra-Low Platinum Loading Membrane Electrode Assembly for PEMFC Commercial Application

Abstract: In this paper, we evaluated the oxygen reduction reaction (ORR) activities of Pt/C, PtCo/C, and PtCoMn/C catalysts using charge-transfer resistance (Rct) and ΔRct onset voltage from electrochemical impedance spectroscopy as indicators in proton exchange membrane fuel cells (PEMFC) over a wide voltage range of 0.66 V∼0.95 V. ORR activity of the PtCoMn/C ternary alloy catalyst is higher than that of Pt/C over a large voltage range. A decal transfer method was used to prepare a membrane electrode assembly (MEA) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 20 publications
(23 reference statements)
0
12
0
Order By: Relevance
“…Results revealed that a Pt catalyst supported by a high surface area TiO 2 /C (25:75) hybrid gave the most outstanding performance. Ultrathin cathode catalyst layers prepared using the decal transfer method containing carbon-supported electrocatalysts Pt/C, PtCo/C, and PtCoMn/C [ 320 ] were evaluated in terms of charge transfer resistance Rct in a single cell. The achieved high performance with MEA with ultralow Pt loading of 0.147 mg/cm 2 was 1.42 W/cm 2 , as shown in Figure 24 .…”
Section: Performance Of Single Monocells—pemfcsmentioning
confidence: 99%
See 1 more Smart Citation
“…Results revealed that a Pt catalyst supported by a high surface area TiO 2 /C (25:75) hybrid gave the most outstanding performance. Ultrathin cathode catalyst layers prepared using the decal transfer method containing carbon-supported electrocatalysts Pt/C, PtCo/C, and PtCoMn/C [ 320 ] were evaluated in terms of charge transfer resistance Rct in a single cell. The achieved high performance with MEA with ultralow Pt loading of 0.147 mg/cm 2 was 1.42 W/cm 2 , as shown in Figure 24 .…”
Section: Performance Of Single Monocells—pemfcsmentioning
confidence: 99%
“… Polarization curves before and after IR free of MEA-PtCoMn/C MEA-PtCo/C and MEA-Pt/C: ( a ) original, ( b ) after IR free. [ 320 ] Reproduced with permission of IOPScience. …”
Section: Figurementioning
confidence: 99%
“…[2,3] Researchers have conducted extensive study on PEMFCs since 2000. In particular, considerable attention has been paid to components that affect fuel cell performance, [4][5][6] life, and durability. [4] A gas diffusion layer (GDL) is an important part of the PEMFC, which is a typical porous material.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, a CL was sprayed on the anode side of the Nafion HP (20 μm) with a Pt loading of 0.05 mg/cm 2 with sizes of 1 cm by 1 cm and 2.5 cm by 2.5 cm. To prepare a single-web cathode, the synthesized Pt/PCA/gCSW2500 was cut with sizes of (52,54,55,60,62) and the (B) MEA performance of the power density (at 0.65 V) and Pt loading at similar conditions (7,30,31,34,38,39,43,44,46,(62)(63)(64)(65)(66)(67)(68). (C) Durability comparisons of the half cell and MEA test results with latest works (8,27,51,62,69,70).…”
Section: Single Carbon Web Mea For Single-cell Testmentioning
confidence: 99%
“…Performance summary. Comparisons with recent works on the (A) half-cell performance of the mass and specific activities at H 2 SO 4 solution(52,54,55,60,62) and the (B) MEA performance of the power density (at 0.65 V) and Pt loading at similar conditions(7,30,31,34,38,39,43,44,46,(62)(63)(64)(65)(66)(67)(68). (C) Durability comparisons of the half cell and MEA test results with latest works(8,27,51,62,69,70).…”
mentioning
confidence: 99%